1996
DOI: 10.2105/ajph.86.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Occupational injury mortality rates in the United States: changes from 1980 to 1989.

Abstract: Changes in occupational injury mortality rates over the 1980s were examined through analysis of the National Traumatic Occupational Fatalities surveillance system. The US occupational injury mortality rate decreased 37% over the decade, with decreases seen in nearly every demographic and employment sector. Greater declines were among men, Blacks, and younger workers, as well as among agricultural, trade, and service workers. Electrocutions, machine-related incidents, and homicides showed the greatest decreases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 3 publications
1
40
1
Order By: Relevance
“…15 Males, Blacks, and older workers were found to have consistently higher death rates than others. Bailer et al, who analyzed NTOF data for the years 1983 through 1992 and adjusted for effects of worker demographics, also found the fatal injury rate for males to be greater than that for females (7.91 vs 0.61 per 100 000).…”
Section: Occupational Fatal Injurymentioning
confidence: 83%
See 2 more Smart Citations
“…15 Males, Blacks, and older workers were found to have consistently higher death rates than others. Bailer et al, who analyzed NTOF data for the years 1983 through 1992 and adjusted for effects of worker demographics, also found the fatal injury rate for males to be greater than that for females (7.91 vs 0.61 per 100 000).…”
Section: Occupational Fatal Injurymentioning
confidence: 83%
“…15,16 Risk has also been found to be much higher for older workers. 17 Some data suggest that African American and Latino workers are at increased risk for fatal occupational injuries.…”
Section: Occupational Fatal Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that machine-related death was the second leading cause of death, both in all industry and agriculture/forestry/fishing. The highest industry-specific rate of machinery-related occupational fatalities in the U.S. was noted in agriculture/forestery/fishing [11][12][13] . Besides motor vehicles, a wide variety of machinery is used in agriculture (tractors, corn pickers, hay balers etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Construction workers risk fatal falls while working from heights (falls from buildings, roofs, ladders or scaffoldings. Falling was the most prevalent cause of death in construction in the U.S. 8,12,15) , as well as in Australia 15) and China 6,16) . This was followed by motor vehicle-related deaths in the U.S. and Australia 15) .…”
Section: Discussionmentioning
confidence: 99%